Software Process and Assistance Modelling: The Case of the UPSSA Tool - Khammaci, T. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1994: Anais do VIII Simpósio Brasileiro de Engenharia de Software, 1994)
Recent works on the software process suggest that the software life cycle should be made through an enactable software process model. This model defines constraints to be respected by a software process during project development and initiatives to be taken by the environment. This paper presents UPSSA : a tool based on a software process model which is an abstraction of objects, tools, and policies. Thus, it encompasses an object model to describe project databases, an operator model to describe at abstract levels the tools’ effects, and characteristics for expressing the policies. Design and implementation are also considered to exhibit how a software process model described in our terms can be used for assisting intelligently the software developer by controlling the software process.